Cellular Consequences of the Initiation of Blood Coagulation - Prydz, Hans; Camerer, Eric; Røttingen, John-Arne; Wiiger, Merete Thune; Gjernes, Elisabet (Thrombosis and Haemostasis, 1999)
This paper reviews some of the cell biological aspects of the consequences of blood clotting initiation. These intracellular events occur in cells carrying tissue factor (TF) when its ligand, factor VIIa, is bound to the receptor-like TF surface molecules. The intracellular signaling generated by this ligand/receptor binding and some of its consequences are described and parallel experiments with factor Xa are discussed.The role of TF as a major player in the initiation of blood coagulation has been known since the last century1,2 and is now characterized in molecular detail. Research on TF, for a long period and for obvious reasons, concentrated on its essential role as a cofactor in this process. Its importance in the development of clinical thrombosis, be it venous or arterial, has been appreciated since it was discovered that monocytes and macrophages3 and endothelial cells,4 under certain conditions, could be induced to synthesize TF. This contributed to answering the previously unresolved question about how TF got into contact with the flowing blood in the absence of any trauma. We later demonstrated that the TF induction process, in many cases, is subject to down-regulation by cAMP5,6 and that Ca2+ influx can induce the synthesis,5,6 along with a large number of other compounds.7 We also showed that protein kinase C was a mediator in at least some of these inducing pathways.8The purification of TF in 19739 showed that TF was an integral membrane protein. By 1977 it was clear that TF likely participated in functions other than blood clotting.10 The cloning of the gene for TF11-14 suggested that, structurally, TF was a member of the Class II cytokine receptor family.15 To fulfil the criteria for being a true receptor, it also needed a specific and high-affinity ligand, which it has in factor VII. Also, to be classified as a true receptor, ligand binding should generate an intracellular signal. In 1992, we presented the first report of such a signal in the form of Ca2+ peaks. These peaks were triggered by the addition of factor VIIa to endothelial cells carrying TF on their surface as a result of exposure to interleukin 1β. These signals were characterized further16,17 and were thought to render final proof for the function of the TF receptor.This review discusses our findings with respect to TF/factor VIIa-induced intracellular Ca2+-signaling and concludes that there is likely a two-component receptor. The more consequential question—whether this intracellular signaling leads to altered gene expression and to other phenotypic changes—is also raised. The establishment of knockout mice18–20 and efforts to solve the three-dimensional structure of this complex by x-ray diffraction21–24 are not reviewed extensively.